2015
DOI: 10.1002/jobm.201400833
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins – prevention and decontamination by yeasts

Abstract: The application of yeasts has great potential in reducing the economic damage caused by toxigenic fungi in the agriculture. Some yeasts may act as biocontrol agents inhibiting the growth of filamentous fungi. These species may also gain importance in the preservation of agricultural products and in the reduction of their mycotoxin contamination, yet the extent of mycotoxin production in the presence of biocontrol agents is relatively less understood. The application of yeasts in various technological processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 126 publications
1
54
0
1
Order By: Relevance
“…Other detoxification practices include gamma radiation and deamination using NaNO 2 . Apart from this, recent research has been investigating to what extent microorganisms, such as lactic acid bacteria and yeasts, may contribute to fumonisin decontamination (Niderkorn, Morgavi, Aboab, Lemaire, & Boudra, ; Pfliegler, Pusztahelyi, & Pócsi, ).…”
Section: Means Of Detoxificationmentioning
confidence: 99%
“…Other detoxification practices include gamma radiation and deamination using NaNO 2 . Apart from this, recent research has been investigating to what extent microorganisms, such as lactic acid bacteria and yeasts, may contribute to fumonisin decontamination (Niderkorn, Morgavi, Aboab, Lemaire, & Boudra, ; Pfliegler, Pusztahelyi, & Pócsi, ).…”
Section: Means Of Detoxificationmentioning
confidence: 99%
“…Generally, there are two groups of probiotics: group one contains the lactic acid bacteria including: Streptococcus , Enterococcus , Lactobacillus , Leuconostoc , Pediococcus , and Bifidobacteria . The second group include the nonlactic acid bacteria contains: Bacillus and the yeast Saccharomyces (Armando, Dogi, & Rosa, ; Darsanaki et al, ; Pfliegler, Pusztahelyi, & Pocsi, ). The two groups of probiotics could be used to prevent different infections including diarrhea, urinary tract infections, cancer, immune disorders, lactose intolerance, and hyper cholesterolaemia, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although some researchers associate Fusarium infection with lower pH values for wort (Oliveira et al, 2012), this was not confirmed in this study, and no significant changes with the increasing degree of infection were detected. yeast can modify and transform mycotoxins from conjugated form to basic and vice versa (Berthiller et al, 2013;Inoue, Nagatomi, Uyama & Mochizuki, 2013;Meng-Reiterer et al, 2015;Nathanail et al, 2016;Pfliegler, Pusztahelyi & Pócsi, 2015). Since nowadays craft and home-brewing gains more and more popularity, and most of these breweries bypass filtration process, it is important to know the quality of raw material and transformation processes of mycotoxins in order to ensure the health safety of such beer.…”
Section: From the Results Inmentioning
confidence: 99%